Is co-invention expediting technological catch up? A study of collaboration between emerging country firms - Elisa Giuliani; Arianna Martinelli; Roberta Rabellotti (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2015)
Firms from emerging countries such as Brazil, India, and China (BIC) are going global, and Europe is attracting around one-third of their direct outward investments. Growing internationalization constitutes an opportunity for technological catch up. In this paper we analyze BIC firms' cross-border inventions with European Union (EU-27) actors, during the period 1990-2012. Our results suggest that cross-border inventions represent an opportunity for BIC firms to accumulate technological capabilities, access frontier knowledge, and appropriate the property rights of co-inventions. This paper contributes to the understanding of the catching up process by emerging country firms, and offers some policy recommendations.
Keywords: 330; Emerging Countries; Multinationals; Technological Catch Up; Patents; European Union